Preliminary Study of Changes in Work Practices of Quantity Surveyors in Building Information Modelling (BIM) Projects - Mokhtar Azizi, Nurul Sakina; Tan , Zi Yu; Azizi, Zahirah (International Journal of Sustainable Construction Engineering and Technology, 2021)
Building Information Modelling (BIM) has been a game changer for the construction industry in transforming how design and construction is delivered. While its introduction aims to increase efficiency in construction, it is unclear what practical changes are affected in the individual work practices of construction players. Many studies have explored the changes in design related work practices, but limited studies have explored the practical changes for quantity surveying (QS) work practices when working in BIM projects. This paper aims to examine the changes in QS work practices according to the RIBA plan of work. The objectives of this paper include i) to identify the positive changes in QS work practices and, ii) to identify the negative changes in QS work practices. Qualitative data were analyzed from the interviews of five Quantity Surveyors with BIM work experience. The analysis revealed that there are six positive changes and four negative changes in QS work practices when involved in BIM projects. The findings from this research can be used to understand the implications of BIM on QS work practices at a practical level and to elucidate the adjustments needed to cope with BIM-related changes.